Cover Picture: Direct Construction of the 9H‐Pyrrolo[1, 2‐a]azepin‐9‐amine Skeleton via [4+3] Annulation of Alkyl 2‐Aroyl‐1‐chlorocyclo‐ propanecarboxylates (Adv. Synth. Catal. 13/2015). Issue 13 (15th September 2015) - Hu, Junhao; Liu, Yang; Gong, Yuefa
<x xml:space="preserve">Abstract</x> The front cover picture, provided by Yuefa Gong and co‐workers, illustrates a highly diastereoselective approach for direct synthesis of the important 9H‐pyrrolo[1, 2‐a]azepin‐9‐amines. This transition metal‐free [4+3] annulation reaction between donor‐acceptor reagents derived from 1H‐pyrrole‐2‐carbaldehydes and alkyl 2‐aroyl‐1‐chlorocyclopropanecarboxylates proceeded quickly under mild basic conditions, affording azepin‐9‐amine derivatives in moderate to high yields with high diastereoselectivities. Details can be found in the communication on pages 2781–2787 (J. Hu, Y. Liu, Y. Gong, Adv. Synth. Catal. 2015, 357, 2781–2787; DOI: 10.1002/adsc.201500376).